Pengaruh Promosi Terhadap Keputusan Pembelian Di Restoran Javana Bistro Bandung - Lina Katrin, Intan; Setyorini, H.p Diyah; haryono, Mas (Universitas Pendidikan Indonesia, 2016)
This research have the the case of descent the segment market that had byJavana Bistro. This cases is happened cause of the competition, as a restaurant in Bandung. So that the efforts that had to make is to increase the decision of purchases consumer in with fixed the promotion program. The purposes of this research is to know the influence of program promotion with decision purchases. Research object is variable (X) Promotion and (Y) Decision Purchases. The method that used in this research is descriftive and verificative with spreaded of assessment to consumers in Javana Bistro. Technique analysis used software SPSS version 22 for windows of this research is regression. The result of this research is that program promotion is influence to decision purchases of consumers in Javana Bistro. Recommendation on this research is Javana Bistro have to increases dimension direct marketing. And also Javana Bistro can fix the choose of product cause this variable had the worst score in this research.